Studyof Unsharp Masking and Contrast Limited Adaptive Histogram Equalization on CT Images of Emphysema - Thomas, Sibu; Shrivas, AK (International Journal of Computer Sciences and Engineering, 2025)
Emphysema is a chronic pulmonary disease caused due to devastation of air sacs present inside the lungs. Emphysema symptoms can be slowed with medications but can’t be cured. Accuracy of diagnosis is very limited and there are several factors behind its misdiagnosis. Poor textural quality is one of thesignificant factors behind poor diagnosis of emphysema. In this article, emphysema images textural quality is enhanced using UnsharpMasking and Contrast Limited Adaptive Histogram Equalization. Result alsosupports a significant increase in contrast improvement of emphysema images. This method potentially suppresses noise and enhances the image contrast as well